The Impact of Utilitarian Value, Hedonic Value, and Brand Image of Modern Coffee Shop City of Malang on Customer Satisfaction - Khalikussabir; Abdul Waris (Jurnal Ekonomi dan Bisnis Jagaditha, 2021)
The existence of modern coffee shops in Malang City is growing and encouraging the birth of coffee shops with all things modern nuances, one of factor is the number of students in Malang City is increasing year by year, so that this moment is used by entrepreneurs to establishing modern coffee shops in the city of Malang, but not all modern coffee shops can maintain their business because competition in introducing or selling products is not oriented to the characteristics of their consumers, this is a challenge for entrepreneurs to be able to understand the characteristics of their consumers well to be able to compete. The purpose of this study is to find out how the impact of utilitarian value, hedonic value, and brand image of modern coffee shops in Malang City on customer satisfaction by using a quantitative descriptive analysis method approach. The results of data analysis show that: 1) utilitarian value behavior that has a consumer has a significant effect on modern coffee shop customer satisfaction; 2) the hedonic value behavior that has consumers has a significant effect on modern coffee shop customer satisfaction; and 3) brand image embedded in consumers has a significant effect on modern coffee shop customer satisfaction.